Study guides

☆☆

Q: What is 3x squared plus 7x plus 2?

Write your answer...

Submit

Still have questions?

Related questions

It is a quadratic expression and can be factored into: (3x+1)(x+2)

3x + (-2 + 4x) = -2 + 7x

simplify it, 7x-12=x+2+2x-3x 7x=2+12+3x-3x 7x=14 x=2

(2x + 1)(3x +2)

The 3x is cubed and the 4x is squared

7x+2 = 3x-2 7x-3x = -2-2 4x = -4 x = -1

(3x+2)-(5+7x) = 3x+2-5-7x = -4x-3 3x+2 is -4x-3 times greater than 5+7x.

You're asking for the difference: (3x + 2) - (5 - 7x).(3x + 2) - (5 - 7x) =3x + 2 - 5 + 7x =10x - 3.It is (10x - 3) greater.

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y

7x+8

5x2+ 7x + 2 = (x + 1)(5x + 2).

7(3y-2)-(-4y+9)

7x + 5 + 3x is [ 10x + 5 ].That's the same thing as [ 2 times (5x + 1) ] .

(3x - y+ 2)(3x + y + 2)

2x2 + 7x + 6 = 2x2 + 4x + 3x + 6 = 2x(x + 2) + 3(x + 2) = (x + 2)(2x + 3)

7x - 2 = 4x + 9 3x - 2 = 9 3x = 11 x = 11/3

(3x+1)(x+2)

(2x - 1)(3x - 2)

x=1

(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y

(3x + 3y)(x + y) = 3(x + y)2

3x2 - 7x = -2 3x2 - 7x + 2 = 0 3x2 - 6x - x + 2 = 0 3x(x - 2) - 1(x - 2) = 0 (x - 2)(3x - 1) = 0 so x - 2 = 0 or 3x - 1 = 0 so x = 2 or x = 1/3

x^2+2x^2=3x^2

(3x - 1)(x + 2)